1981
DOI: 10.1111/j.1471-0528.1981.tb00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Bile Acid Concentrations During Normal Pregnancy, in Patients With Intrahepatic Cholestasis of Pregnancy and in Pregnant Women With Itching

Abstract: SummaryTwo primary bile acids, cholic acid (CA) and chenodeoxycholic acid (CDCA), and one secondary bile acid, deoxycholic acid (DCA), were measured by radioimmuno‐assay in pregnancy serum from 30 healthy women, 49 women with itching and 45 with intrahepatic cholestasis of pregnancy. All subjects were studied serially from between 16 and 20 weeks gestation until 35–60 days post partum. In healthy pregnant women, serum CA and DCA levels did not change significantly at any time. The mean CDCA level rose signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(71 citation statements)
references
References 16 publications
2
68
0
1
Order By: Relevance
“…20,21,24,25 We found tBA to be increased in 63%, ALT in 64%, and AST in 80% of women with ICP (at diagnosis), whereas others have reported tBA and ALT to be elevated in 92% to 100% and 50% to 100% of ICP cases, respectively. 1,20,21,26 Part of this variability highlights the problem of a consistent definition for ICP, particularly in earlier series. The magnitude of elevations in tBA were lower than those of ALT activity or GSTA concentrations in our study, further supporting the use of the latter.…”
Section: Discussionmentioning
confidence: 74%
“…20,21,24,25 We found tBA to be increased in 63%, ALT in 64%, and AST in 80% of women with ICP (at diagnosis), whereas others have reported tBA and ALT to be elevated in 92% to 100% and 50% to 100% of ICP cases, respectively. 1,20,21,26 Part of this variability highlights the problem of a consistent definition for ICP, particularly in earlier series. The magnitude of elevations in tBA were lower than those of ALT activity or GSTA concentrations in our study, further supporting the use of the latter.…”
Section: Discussionmentioning
confidence: 74%
“…Although liver transaminases can be elevated in ICP, total serum bile acid concentration appears to be the most specific laboratory evidence for the presence of ICP. 21,22 To our knowledge, there is no validated method to measure pruritus in ICP. Our decision to use a 10-point visual analog scale was to provide our subjects an easy unidimensional method to rate their pruritus; pruritus is most commonly measured using a 10-point scale.…”
Section: Resultsmentioning
confidence: 99%
“…In normal pregnancy, serum bile acid levels do not change significantly during the course of the pregnancy, 22,23 although one study has reported reduced levels in the first trimester. 24 Cholic acid is the primary bile acid in pregnant women, while chenodeoxycholic acid and deoxycholic acid predominate in nonpregnant women.…”
Section: Discussionmentioning
confidence: 99%